Revealing the hidden effects of land grabbing through better understanding of farmers’ strategies in dealing with land loss - Suhardiman, Diana; Giordano, Mark; Keovilignavong, Oulavanh; Sotoukee, Touleelor (Elsevier, 2015)
This article examines changing contexts and emerging processes related to “land grabbing.” In particular, it uses the case of Laos to analyze the driving forces behind land takings, how such drivers are implied in land policies, and how affected people respond depending on their socio-economic assets and political connections. We argue that understanding the multiple strategies farmers use to deal with actual land loss and the risk of losing land is crucial to understanding the hidden effects of land grabbing and its potential consequences for agricultural development and the overall process of agrarian transformation. From a policy perspective, understanding the hidden effects of land grabbing is critical to assess costs and benefits of land concessions, in Laos and elsewhere, especially in relation to current approaches to turn land into capital as a policy strategy to promote economic growth and reduce poverty.